KOMUNIKASI ANTARBUDAYA DALAM TATA KRAMA BUDAYA DAN BAHASA - Putu Budiyasa, I Dewa Gede (Widya Duta: Jurnal Ilmiah Ilmu Agama dan Ilmu Sosial Budaya, 2018)
Culture and communication are important links to understanding intercultural communication. Cultural resemblance greatly influences the customs, codes, and languages used. Communication and culture reveal individual communication behaviors cared for in a particular culture. Culture is a comprehensive lifestyle while language is a means of communication between members of the public in the form of sound symbols produced by human speech utensils. Through language, humans can adjust to the customs, behavior, public manners and at the same time easily mix themselves with all forms of culture that developed in society.